Optimization of Nickel Coating Thickness on Copper via Ultrasonic-Assisted Electroplating - Sendie Yuliarto Margen; Yusuf Subagyo; Keysia Manda; Candra Kurniawan; Fariz Wisda Nugraha; Imaduddien Ariefa; Komar Roni; Rieky Handoko; Anton Harseno; Sahal Ahmad Albab; Yuris Bahadur Wirawan; Baharudin Priwintoko; Agus Prasetyo (Multidisciplinary Innovations and Research in Applied Engineering, 2026)
This study provides a preliminary descriptive comparison of nickel coating thickness deposited on copper at a fixed current of 1.5 A and an electrolyte temperature of 45 °C for 60, 120, and 180 s, with and without assistance from a nominal 40 kHz ultrasonic bath. The Watts electrolyte contained nickel sulfate 300 g/L, nickel chloride 30 g/L, boric acid 30 g/L, brightener I 15 mL/L, and brightener II 1 mL/L. Based on the specimen dimensions shown in the experimental schematic and assuming that both broad faces were exposed, the nominal cathode area was approximately 29.82 cm² and the nominal current density was 5.03 A/dm²; this estimate excludes edge area and remains uncertain because masking and actual immersion were not documented. The reported local cross-sectional thickness increased from 4.76 to 8.27 µm without ultrasound and from 8.34 to 13.43 µm with ultrasonic-bath assistance as deposition time increased. Descriptive linear fits across the three time points gave R² values of 0.9995 and 0.9991, respectively. The ultrasonic-assisted values were 62.4–75.2% higher than the corresponding conventional values. Because the archived dataset contains one reported mean per condition based on repeated measurement locations rather than documented independent specimens, statistical significance, optimization, current efficiency, adhesion, uniformity, and overall coating quality are not claimed. The findings therefore constitute preliminary evidence that longer deposition time and ultrasonic-bath assistance were associated with higher locally measured nickel thickness under the reported conditions.